PEMBENTUKAN JIWA ENTREPRENEURSHIP BAGI PARA ISTRI NELAYAN MELALUI PELATIHAN PEMBUATAN GREEBLE CHIPS - Anggia Sari Lubis (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2018)
The concept of entrepreneurship is present to increase economic growth in Indonesia. Kuala Lama Village Serdang Bedagai is 60 Km from Medan City or 8 Km from Sei Rampah (the capital of Serdang Bedagai Regency). The main livelihoods of the population are as farmers and fishermen. Training materials include: brief lectures to motivate fisherman's wives, nature and characteristics of fresh green vegetables;how to processed the green vegetables into packaged food products named Greeble Chips. The expected target of this activity is to help improving the skills of fisherman wife in Kuala Lama Village, Pantai Cermin Subdistrict, in processing the green vegetables into a durable food packaging and have high selling value. The output of this activity is green vegetable processed products named Greeble Chips. The real result in this activity is to produce green processed products named green vegetable chips (greeble chips), business assistance, motivation and increasing skills and understanding of marketing strategy and simple financial report. Keywords: Creation of Entrepreneurship Spirit, Greeble Chips